The Frequency of the Retinopathy in Patients of Chronic Hepatitis C Treated with Interferon Alpha - Ribavirin Combination Therapy (Journal of Fatima Jinnah Medical University, 2018)
Objectives: Chronic hepatitis C causes cirrhosis of liver in 20% of the total 170 million people affected and is the commonest cause of hepatocellular carcinoma as well. Treatment of hepatitis C with interferon- ribavirin combination therapy has proved to be effective in terms of biochemical and virological response. Retinopathy is a well-recognized side effect of interferon therapy. Cases have been reported where patients of chronic hepatitis C being treated with interferon suffered from blindness. Surveillance for this side effect of interferon has not been done strictly in the past. The objective of the study is to elucidate the frequency of retinopathy in patients of chronic hepatitis C who are on conventional interferon alpha- ribavirin combination therapy.Design: Descriptive case series.Place and duration of study: The study was conducted in Hepatitis Clinic, Medical Unit III Services Hospital Lahore. The study was carried out over a period of six months, from 25th August 2010 to 25th Feb. 2011.Method: One hundred and fifty patients were included in the study. Interferon and ribavirin combination therapy was then started in the dose of 3 million units subcutaneously thrice a week and 400mg orally thrice a day respectively. Fundoscopy was done by a single ophthalmologist in every patient after the week 6 and 12 of the start of therapy. Presence or absence of retinopathy was documented.Results: One hundred and fifty patients were enrolled in the study. Eighty eight patients (58.7%) were male and 62 (41.3%) female. Ages of the patients ranged between 20-50 years with the mean age 37 ± 7.907 years. One hundred and sixteen patients (77.3%) did not develop any retinal changes but remaining 34 patients (22.7%) suffered from retinopathy.Conclusion: It is concluded that every patient on interferon therapy should have regular eye examination for surveillance of retinopathy to prevent blindness, a dreadful consequence
Keywords: Interferon, retinopathy and chronic hepatitis C